The word ‘UniverCITY’ is a combination of two words, university and city, to symbolize integration of universities in the city as coined by the author - Gachuki, Jerry Munene (My University, 2020)
The 21st century has brought about numerous interventions and innovation in planning and design of cities globally. With such evolved systems, planning and design of universities within the urban fabric needs to shift focus from an introverted design approach to one that is more integrated with urban design in terms of connectivity, permeability, robustness, variety and richness. Universities as heavy contributors to the cities in terms of service and intellect seem to respond more to security and introversions than to integration with the built environment within the city. This research attempted to interrogate and question the role universities play in the growth of cities in the 21st century. A comprehensive study of the Tshwane University of Technology, Arts and Arcadia campuses in Pretoria, Gauteng, South Africa was explored. The approach was primarily done through a qualitative study approach that focused on research by design. This was followed by research methods of observations, photography, videography, sketches, detailed plans and 3d models in order to apply the theories and principles addressed during the literature review and case studies
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Urban Design, 2020
Keywords: College buildings; Campus planning